Management of Phenytoin Induced Gingival Overgrowth: A Case Report - Vijay Lal; T Prasanth; Pramod (Journal of Orofacial Research, 2021)
Gingival hyperplasia/ hypertrophy/ overgrowth are common terms used to describe any type of enlargement of gingiva. This overgrowth can be associated with various etiological reasons. Accordingly, it has been classified into different subheads. This can either be localised or generalised, papillary, or marginal depending on the area affected and diffuse or discrete. Inflammatory enlargements can be acute or chronic. Factors may range from inflammation due to local biofilm to neoplastic enlargements. Studies have also attributed gingival overgrowth to be associated with certain drugs (anticonvulsants, immunosuppressants and calcium channel blockers). This case report narrates the management of phenytoin induced gingival overgrowth using external bevel gingivectomy to achieve desirable esthetics.